Carbon nanotube film synthesized from ethanol and its oxidation behavior in air - 任彦 马文君 曾庆圣 李金柱 董海博 周维亚 (Chinese physics B, 2012)
In this paper, we propose an efficient way to synthesize carbon nanotube films using ferrocene and ethanol. The as-grown film is free-standing, semi-transparent, and of macro scale size. The tubes in the film are mostly single- or double-walled. The oxidation behavior of the film is studied via Raman spectroscopy, and the result indicates that the inner wall of the double-walled tube is effectively protected from oxidation by the outer wall.